Assessment of electrified ethylene production via biomass gasification and electrochemical CO reduction - Klüh, Daniel; Nieminen, Harri; Melin, Kristian; Laari, Arto; Koiranen, Tuomas (Frontiers in Energy Research, 2023)
The chemical industry needs new methods for sourcing carbon-containing feedstocks from renewable sources to decrease CO2 emissions and reduce reliance on fossil fuels. Ethylene, a crucial base chemical used for making polymers and ethylene oxide, is primarily produced through steam cracking of fossil feedstocks.. However, an evolving technology is the electrochemical reduction of CO2 or CO to produce ethylene. The study assesses the environmental, economic and energetic performance of a new biomass-based process that produces ethylene based on the electrochemical reduction of CO. The results are based on mass and energy balances from process simulation. The CO is produced by either gasification of biomass or combustion of biomass with CO2 capture and CO2 electrolysis. Besides ethylene, the process produces acetic acid, ethanol, oxygen and hydrogen as by-products which are purified and sold. The annual output varies between 36 and 68 kt ethylene with a biomass input of 157 kt. The levelized cost of ethylene ranges from 3920 to 7163 €/t with the gasification routes being the most cost-effective. The ethylene price is heavily dependent on electricity price, current density, operating voltage, and by-product prices. The carbon efficiency of the gasification-based routes is lower (64 %) than the combustion-based routes (85 – 86 %). However, the energy efficiency is higher for the gasification-based routes (42 %) compared to the combustion-based routes(28 %). Conversion of ethanol to ethylene increases the ethylene yield with minimal impacts on the ethylene price. In terms of CO2 emissions, the gasification-based routes show lower emissions. Scenarios using wind power show a significant emission reduction potential compared to fossil products.